Researching glutamate – induced cytotoxicity in different cell lines: a comparative/collective analysis/study - Kritis, Aristeidis A.; Stamoula, Eleni G.; Paniskaki, Krystallenia A.; Vavilis, Theofanis D. (Frontiers in Cellular Neuroscience, 2015)
Although glutamate is one of the most important excitatory neurotransmitters of the central nervous system, its excessive extracellular concentration leads to uncontrolled continuous depolarization of neurons, a toxic process called, excitotoxicity. In excitotoxicity glutamate triggers the rise of intracellular Ca2+ influx, followed by up regulation of nNOS, dysfunction of mitochondria, ROS production, ER stress and release of lysosomal enzymes. Excessive calcium concentration is the key mediator of glutamate toxicity through over activation of ionotropic and metabotropic receptors. In addition, glutamate accumulation can also inhibit cystine uptake by reversing the action of the cystine/glutamate antiporter. Reversal of the antiporter action reinforces the aforementioned events by depleting neurons of cysteine and eventually glutathione’s reducing potential. Various cell lines have been employed in the pursuit to understand the mechanism(s) by which excitotoxicity affects the cells leading them ultimately to their demise. In some cell lines glutamate toxicity is exerted mainly through over activation of NMDA, AMPA or Kainate receptors whereas in other cell lines lacking such receptors, the toxicity is due to glutamate induced oxidative stress. However in the greatest majority of the cell lines ionotropic-glutamate receptors are present, co-existing to cystine/glutamate antiporters and metabotropic glutamate receptors, supporting the assumption that excitotoxicity effect in these cells is accumulative. Different cell lines differ in their responses when exposed to glutamate. In this review article the responses of PC12, SH-SY5Y, HT-22, NT-2, OLCs, C6, primary rat cortical neurons, RGC-5 and SCN2.2 cell systems are systematically collected and analyzed.